RENEWABLE ENERGY AND IT’S ROLE IN EXPENDING ACCESS TO ELECTRICITY AND ECONOMIC GROWTH IN NIGERIA - Demola Salami Olatokunbo; Samuel Gbemisola Olajide; Mladen Ivic (STED Journal)
The study investigated, amongst other variables, the relationship between renewable energy, its role in expanding access to electricity, and economic growth in Nigeria over the period 1960–2023. The ordinary least squares (OLS) and autoregressive distributed lag (ARDL) models were used to estimate the short- and long run dynamics of the relationship. The study shows that the overall model is statistically significant, meaning that the independent variables, taken together, significantly predict the dependent variable (GDP growth rates). The findings underline the intricate dynamics between renewable energy, electricity access, and economic growth in Nigeria. While the positive coefficient for renewable energy suggests that increasing renewable electricity generation could theoretically enhance GDP growth, the lack of statistical significance implies that this impact is not immediate. Finally, based on these findings, the study recommends that policymakers should continue to prioritize investments in renewable energy infrastructure. Efforts should be made to enhance the reliability and quality of the electricity supply. A more robust and cohesive policy framework is needed to support renewable energy and electricity development and integration.